1998
DOI: 10.1152/ajpcell.1998.274.5.c1373
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of ENaCs: insulin and aldosterone

Abstract: Although a variety of hormones and other agents modulate renal Na+ transport acting by way of the epithelial Na+ channel (ENaC), the mode(s), pathways, and their interrelationships in regulation of the channel remain largely unknown. It is likely that several hormones may be present concurrently in vivo, and it is, therefore, important to understand potential interactions among the various regulatory factors as they interact with the Na+transport pathway to effect modulation of Na+ reabsorption in distal tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
146
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 25 publications
(50 reference statements)
12
146
2
1
Order By: Relevance
“…The effects of aldosterone and insulin or IGF-1 may be additive [17]. Insulin stimulates SGK1 and is thus expected to enhance ENaC activity and renal Na + reabsorption [6][7][8]. SGK1 contributes to the regulation of renal Na + excretion by aldosterone, insulin, and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of aldosterone and insulin or IGF-1 may be additive [17]. Insulin stimulates SGK1 and is thus expected to enhance ENaC activity and renal Na + reabsorption [6][7][8]. SGK1 contributes to the regulation of renal Na + excretion by aldosterone, insulin, and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…One effect of insulin signaling in the gut is the upregulation of ENaC receptors and the increase of ENaC's permeability. 96 Reversetranscription polymerase chain reaction data have revealed that taste cells express the insulin receptor. 75 Furthermore, patch-clamp studies revealed that sodium þ influx increased significantly upon insulin administration in ENaC-responsive taste cells.…”
Section: Insulinmentioning
confidence: 99%
“…Examples include the cAMP-induced insertion of the cystic fibrosis transmembrane conductance regulator (CFTR; ref. 3) and the promotion of delivery of epithelial Na ϩ channels to the apical membrane by aldosterone and insulin (4,5). Also, hypoosmotically induced swelling of renal epithelial cells was found to result in the insertion of Na ϩ channels into the plasma membrane (6).…”
mentioning
confidence: 99%